2006
DOI: 10.2116/analsci.22.1425
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Uranium from Simulated Ore by the Supercritical Carbon Dioxide Fluid Extraction Method with Nitric Acid-TBP Complex

Abstract: Uranium used for the uranium fuel of nuclear power plants is obtained from uranium ores having relatively high uranium content by extraction and separation. However, generally utilized ores, such as monazite, phosphate rock, and titanium ore, are not uranium ores, but include a small amount of uranium. In order to determine uranium content in these ores, uranium is first separated out by leaching ores with mineral acids, and then uranium in the leaching solution is determined by inductively coupled plasma mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The supercritical fluid extraction (SFE) method using CO 2 as a medium with an extractant of HNO 3 -tri-n-butylphosphate complex was applied by Dung et al [241] to extract uranium from several uranyl phosphate compounds and simulated uranium ores. They found that uranium could be efficiently extracted from both the uranyl phosphates and simulated ores.…”
Section: Extraction With Solvents and Supercritical Fluidsmentioning
confidence: 99%
“…The supercritical fluid extraction (SFE) method using CO 2 as a medium with an extractant of HNO 3 -tri-n-butylphosphate complex was applied by Dung et al [241] to extract uranium from several uranyl phosphate compounds and simulated uranium ores. They found that uranium could be efficiently extracted from both the uranyl phosphates and simulated ores.…”
Section: Extraction With Solvents and Supercritical Fluidsmentioning
confidence: 99%